2022
DOI: 10.3389/fnut.2022.888047
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis for the Removal and Transformation of Pesticide Residues During Food Processing: A State-of-the-Art Minireview

Abstract: Pesticide residues are of great significant issue that exerted adverse effects on humans. There is a need for effective and non-toxic decontamination of pesticide residues during food processing. In this minireview, the recent advances in the degradation of pesticide residues by photolysis have been firstly described during food processing. The mechanisms of pesticide residues destruction by photolysis were discussed accordingly. Finally, applications of photolysis in the degradation of pesticide residues from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Pesticides are a significant issue that harms society (Xiao et al, 2022). Whereas most pesticides are potentially toxic to humans, resulting in serious health consequences (Wallace & Djordjevic, 2020), and large amounts of pesticides can cause DNA damage (Isah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides are a significant issue that harms society (Xiao et al, 2022). Whereas most pesticides are potentially toxic to humans, resulting in serious health consequences (Wallace & Djordjevic, 2020), and large amounts of pesticides can cause DNA damage (Isah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting study showed that the rate of degradation of malathion by UV light alone was lower than that observed when photocatalytic treatments, such as UV/H 2 O 2 , UV/TiO 2 , and UV/Fenton systems, were applied; however, in contrast to the photocatalytic processes, no increase in toxicity of the malathion aqueous solution after UV irradiation alone was observed [175]. Therefore, it is assumed that applications of photocatalytic oxidation in food processing can be limited due to the observed toxicity of the treated solutions [147].…”
Section: Abiotic Degradation Strategymentioning
confidence: 95%
“…The chemical methods for the oxidative degradation of OPs mainly include the utilization of the various chemical oxidants, such as ferrate (VI), manganese dioxide, manganese dioxide charged with bisulfite, and nano-structured titania-iron mixed oxides, which provided encouraging results in environmental remediation, especially treatments of water [143][144][145][146]. However, limited effects of chemical techniques on pesticide removal rates are also reported [147].…”
Section: Abiotic Degradation Strategymentioning
confidence: 99%
See 1 more Smart Citation